Significant Factors Affecting the Cooperative’s Profits in Eastern Indonesia: A Quantitative Analysis - Muhammad Syaiful; Abdullah Igo; Sapriyadi; Yuyun Anggraini; Hariono; Kartomo; Ulan Mutmainnah Buchari (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study examines the impact of own capital, loan capital, and business volume on the profits of special cooperatives in Eastern Indonesia from 2017 to 2020. Conducted as a descriptive quantitative causal study, it utilizes secondary data obtained from the Ministry of Cooperatives, covering cooperative data from the specified years. Data collection involved downloading annual data on Indonesian cooperatives and selecting variables relevant to the study, including own capital, loan capital, business volume, and cooperative profits. Data analysis employed multiple regression tests to assess the relationships between the dependent variable and multiple independent variables, preceded by classical assumption tests. The findings reveal that own capital and business volume positively influence cooperative profits, while loan capital has a negative effect. Collectively, the independent variables significantly impact cooperative profitability. These findings contribute to decision-making processes for cooperatives in Eastern Indonesia, providing a foundation for refining financial strategies and enhancing operational effectiveness.